EFEKTIVITAS MANAJEMAN MADRASAH - Prayuni, Ary (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2024)
The concept of MBM provides quite ideal direction to Islamic educational institutions called madrasas. Because with MBM madrasah can manage all existing madrasah management, both finance, persoanalia, infrastructure, class and public relations. With MBM madrasah can advance in quality according to the goals set by each madrasah, of course, these goals are above the standard goals set by the Ministry of Agriculture, as the ministry responsible for the success of madrasah education. Thus, when MBM can run effectively in each madrasah, madrasah competition to achieve quality goals is very possible, commanded by a strong and professional madrasah head.